Pengaruh Pembelajaran Inquiri Terbimbing Berbasis Socioscientific Issue Terhadap Kemampuan Scientific Reasoning Peserta Didik di MTs Negeri 7 Madiun - Nur Aini Purwaningrum; Hanin Niswatul Fauziah (LP. Ma'arif Janggan Magetan, 2022)
This study aims to determine the effect of the guided inquiry learning model based on the socioscientific issue on the scientific reasoning ability of students at MTs Negeri 7 Madiun. The research sample consisted of class VII A as the experimental class and class VII D as the control class which were taken randomly with a total of 64 students. Data was taken by distributing tests to students before and before the implementation of the learning model. The learning model applied to the control class is the lecture learning model, while the learning model in the experimental class is a guided inquiry learning model based on socioscientific issues. The data obtained were then analyzed by t-test. The results showed that the guided inquiry model based on the socioscientific issue had an effect on students' scientific reasoning abilities. This is based on the value of the t test results which show a significance value of 0.00.